Intra-abdominal hypertension as a risk factor for acute kidney injury in geriatric - Momot, N. V.; Vorotyntsev, S. I.; Воротинцев, Сергій Іванович (My University, 2024)
Intra-abdominal hypertension is an often underestimated risk factor for acute kidney injury (AKI). But the values of intra-abdominal pressure (IAP) and abdominal perfusion pressure (APP), which are critical for the development of AKI in elderly patients after urgent abdominal surgery, are still not defined. Objective. To evaluate the relationship between IAP and APP and the development of acute kidney injury in geriatric patients after emergency abdominal surgery. Materials and methods. A prospective single-center study included 66 patients older than 60 years who underwent surgery for peritonitis and were transferred to the intensive care unit. Statistical processing was performed using the program "STATISTICA for Windows 13" (StatSoftInc., No. JPZ804I382130ARCN10-J). Results. Among the examined patients, 48 developed AKI (73%). The average values of IAP in patients with AKI and without AKI were 10.4 (7.4, 13.3) mm Hg and 6.7 (4.4; 9.6) mm Hg respectively (p<0.0001). APP in patients with AKI, respectively, was significantly lower (72 (61.5, 83.7)) than in patients without AKI (85.6 (74.5, 94.4; p<0.0001)). According to the results of logistic regression analysis, a relationship between high IAP values and the development of AKI was revealed: the odds ratio (OR) was 3.4 with the value of the criterion x2=32.4 (р<0.0001). The odds ratio between the reduction of APP and the development of AKI was 2.3 with the value of the criterion x2=13.4 (p=0.0002).ROC analysis showed that IAP>10.4 mm Hg. is the threshold level for the development of AKI with a sensitivity of 46% and a specificity of 90.5%, with an area under the AUC curve of 0.74 (p<0.001). APP<79.12 mm Hg is critical for the development of AKI, with a sensitivity of 66.4% and a specificity of 70%, with an area under the AUC curve of 0.68 (p<0.001). Conclusions. High values of IAP and reduction of APP are associated with the occurrence of acute kidney injury in elderly patients after emergency abdominal surgery.
Keywords: geriatric patients; acute kidney injury; intra-abdominal hypertension